Evaluation of LEED Requirements for Site Properties in Developing Country-Specific Certification - Komurlu, Ruveyda; Gurgun, Asli Pelin; Arditi, David (ELSEVIER SCIENCE BV, 2015)
Construction activities are strongly affected by the properties of the site. Site conditions direct the investment decision and development approach. Leadership in Energy and Environmental Design (LEED), the most widely used certification system around the world, covers site properties with two sections, i.e., Location and Transportation, and Sustainable Sites. These two sections in LEED v4 NC add up to 42 points, which corresponds to approximately 33.3% of the total points that a building can receive. Issues such as neighborhood development location, sensitive land protection, high priority site, surrounding density and diverse uses, access to quality transit, bicycle facilities, reduced parking footprint, and green vehicles that are treated in the Location and Transportation section have different priorities and implications in developing countries. Similarly, issues such as pollution prevention, site assessment, site development - protect or restore habitat, open space, rainwater management, heat island reduction, and light pollution reduction that are treated in the Sustainable Sites section are based largely on local practices and standards, and therefore offer different challenges. In this study, these two sections of LEED v4 NC are assessed relative to practices in developing countries. A comparative review of the topics is performed by means of a thorough literature survey. It is expected that the outcome of the study will provide guidance to professionals in selected developing countries towards improvement of the existing state and practices. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Developing Countries; LEED; Sustainable Sites; Location and Transportation; ENERGY; CONSTRUCTION; Science & Technology - Other Topics; Engineering